Negotiating Linguistic and Religious Diversity A Tamil Hindu Temple in Australia - Perera, Niru (Routledge, 2022)
Based on a sociolinguistic ethnography in a Tamil Saivite temple in Australia, the book explores the challenges for the institution in maintaining its linguistic and cultural identity in a new context.